2020
DOI: 10.1371/journal.pone.0241333
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular trap components and myocardial recovery in post-ischemic acute heart failure

Abstract: Objective The role of neutrophil extracellular traps (NETs) in acute heart failure is unknown. We recently showed that interleukin 8, a putative NETs stimulator, was associated with myocardial recovery in acute heart failure complicating ST-elevation myocardial infarction (STEMI). In this exploratory post-hoc study, we aimed to investigate the role of NETs components in relation to myocardial function and interleukin 8 in STEMI patients with symptomatic acute heart failure. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Particularly, CE clots have higher web-like NETs expression compared to both AT and cryptogenic clots, in accordance with the earlier findings [18,20,21]. A number of studies have shown that identification of circulating NETs in the blood is possible through detecting double-stranded DNA (dsDNA), MPO-DNA, citrullinated histones, and peptidyl arginine deiminase 4 (PAD4) [39,40]. Vallés et al demonstrated that plasma markers of NETs like CitH3 are significantly higher is AIS patients with undesirable outcomes demonstrating a potential prognostic value [41].…”
Section: Discussionsupporting
confidence: 86%
“…Particularly, CE clots have higher web-like NETs expression compared to both AT and cryptogenic clots, in accordance with the earlier findings [18,20,21]. A number of studies have shown that identification of circulating NETs in the blood is possible through detecting double-stranded DNA (dsDNA), MPO-DNA, citrullinated histones, and peptidyl arginine deiminase 4 (PAD4) [39,40]. Vallés et al demonstrated that plasma markers of NETs like CitH3 are significantly higher is AIS patients with undesirable outcomes demonstrating a potential prognostic value [41].…”
Section: Discussionsupporting
confidence: 86%
“…For example, it would be of interest to establish the association of co-morbidities (malignancy, diabetes) with the VWF/fibrin/DNA content of thrombi, but this analysis requires a larger size sample. In view of the recent data that following interventional treatment of acute myocardial infarction NET-biomarkers in blood are partly correlated with myocardial recovery [53], our results S2) with 95% confidence intervals (dotted lines) is shown for CAD and AIS patients with atherosclerosis (in green; cross symbols show outliers identified as described in [39]). Red symbols: CAD and AIS patients without any signs of atherosclerosis and all PAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that C-reactive protein induces a concentration-dependent NET synthesis in patients with heart failure [ 50 ]. A link has been proposed between NETs-related coronary microvascular and macrovascular thrombosis through some possible mechanisms, involving mitochondrial DNA, high-mobility group box 1, fibronectin extra domain A, and galectin-3 and pattern recognition receptors, leading to the increase of heart failure [ 51 , 52 , 53 , 54 ].…”
Section: Neutrophil Extracellular Traps (Nets): Introduction Mechanis...mentioning
confidence: 99%